2021
DOI: 10.15376/biores.17.1.616-633
|View full text |Cite
|
Sign up to set email alerts
|

Seed propagation, adaptation to cultivation conditions, determination of ornamental plant properties, and ex situ conservation of the endemic species Centaurea hermannii F. Hermann

Abstract: This study focused on seed propagation and ex situ conservation of the endemic species Centaurea hermannii F. Hermann. Plant properties such as vegetation cycle, adaptation to the cultivation environment, morphological characteristics of the plants and seeds, and esthetic properties as an ornamental variety were investigated. The percentage of viability of the seeds, as well as the effects of different seed germination methods when applied to the germination speed, were also explored. C. hermannii specimens pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…Our results confirm the information that cold–wet stratification (Russell, 2011) and GA 3 treatments (Del Egido et al, 2019; Kildisheva et al, 2019) are effective in dormant seeds without water penetration problems. Kırmızı et al (2018) and Yucel (2022) reported results parallel to our study. Kırmızı et al (2018) revealed that GA 3 and cold–wet stratification promoted seed germination by breaking dormancy in L. olympicum seeds.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results confirm the information that cold–wet stratification (Russell, 2011) and GA 3 treatments (Del Egido et al, 2019; Kildisheva et al, 2019) are effective in dormant seeds without water penetration problems. Kırmızı et al (2018) and Yucel (2022) reported results parallel to our study. Kırmızı et al (2018) revealed that GA 3 and cold–wet stratification promoted seed germination by breaking dormancy in L. olympicum seeds.…”
Section: Discussionsupporting
confidence: 91%
“…Kırmızı et al (2018) revealed that GA 3 and cold–wet stratification promoted seed germination by breaking dormancy in L. olympicum seeds. Yucel (2022) also reported very similar results to our study. The researcher achieved the best germination results from combinations of cold–wet stratification and GA 3 treatments in Centaurea hermannii seeds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The seeds were approximately 4.48 x 1.71 mm in size, 1000 kernel weight was 3.2 g, and there were an average of 311.7 seeds per 1 g. Considering C. olympica seed structure, Eroğlu et al (2014) and Tel et al (2019) stated that the seed size of C. hermannii is 4 to 5 mm. Yücel (2022) From the seeds collected at the populations around Yalova Teşvikiye village in 2019, the net viability rate was 76.7%. However, this rate can vary greatly according to the years and the time of collection of the seeds.…”
Section: Determination Of Morphological Phenological and Biological C...mentioning
confidence: 99%
“…Different results have been reported for the viability studies of Centaurea species. For example; Yücel (2022) determined the viability rate for C. hermannii seeds as 72.22%, while Atasagun and Aksoy (2018) determined 82% for C. amaena seeds, Yankova-Tsvetkova et al (2018) found this rate to be 17.5% for C. achtarovii, Özel and Khawar (2006) found 85% for C. tchihatcheffii, and Emek and Erdağ (2012) reported 80% viability for Rhaponticoides mykalea species. All these reports revealed that the viability rates can vary significantly according to species, years, and environmental conditions.…”
Section: Determination Of Morphological Phenological and Biological C...mentioning
confidence: 99%